2021
DOI: 10.3390/nursrep11030066
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perceptions of the Factors Contributing to the Development of the Love of the Profession: A Qualitative Content Analysis

Abstract: As a professional value, the love of the profession can significantly affect nurses’ professional practice, behaviors and commitment. Many different factors can affect the love of the profession. The exploration of nurses’ experiences of these factors can provide valuable data for development of the love of the profession. The aim of this study was to explore nurses’ perceptions of the factors contributing to the development of the love of the profession. This qualitative study was conducted in 2020–2021 using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Then, as indicated by our participants and together with the findings of other studies, learning and using nursing theories in clinical practice would provide nurses and nursing students with a rationale for their practice, improve their professional autonomy, increase the quality of care, 10 improve their professional image, increase their interest in the nursing profession, and induced in them a greater sense of satisfaction with being a nurse. A recent qualitative study of Iranian nurses also examined the factors contributing to the development of the love of the nursing profession and categorized these factors into four main categories, namely the public perception of the profession, educational variables, the characteristics of the profession, and nurses' self‐evaluation 59 . Educational variables included the applicability and usefulness of nursing courses and the knowledge, accountability, and character of nursing educators.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, as indicated by our participants and together with the findings of other studies, learning and using nursing theories in clinical practice would provide nurses and nursing students with a rationale for their practice, improve their professional autonomy, increase the quality of care, 10 improve their professional image, increase their interest in the nursing profession, and induced in them a greater sense of satisfaction with being a nurse. A recent qualitative study of Iranian nurses also examined the factors contributing to the development of the love of the nursing profession and categorized these factors into four main categories, namely the public perception of the profession, educational variables, the characteristics of the profession, and nurses' self‐evaluation 59 . Educational variables included the applicability and usefulness of nursing courses and the knowledge, accountability, and character of nursing educators.…”
Section: Discussionmentioning
confidence: 99%
“…Educational variables included the applicability and usefulness of nursing courses and the knowledge, accountability, and character of nursing educators. Characteristics of the profession also included the usefulness of nursing and the existence of a specialized body of knowledge 59 . Some studies also analyzed a number of nursing theories and concluded that nursing theories can be used not only to guide nurses' practice—even in the COVID‐19 pandemic—but also can serve as a guide in the development and evaluation of a hospital‐based programs to support nurses and improve their group identity 60,61 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier, we examined the factors contributing to the development of the lop and have reported that the public perception of the profession, educational variables, characteristics of the profession, and nurses’ self-evaluation effectively develop the lop in nurses. Although in that report several nurses cited the impact of social factors on the development of the lop [ 15 ]. However, the environmental and organizational factors affecting the development of lop in nurses have not been assessed.…”
Section: Introductionmentioning
confidence: 99%